Chemical characteristics of the Bandaiko hyper-acidic hot spring in Kusatsu Town, Gunma prefecture, and evaluation test of scale for binary power generation - Mio Ichino; Toshio Inoue; Yuka Kubotsu; Hideo Takizawa; Yukiko Hoshino; Daisuke Tanaka; Akira Ueda; Hideki Kuramitz (Geothermics, 2027)

Interactions between basalt and CO2-saturated water at varying temperatures (100°C–300 °C) in a duplex reactor - Heejun Yang; Akira Ueda; Hideki Kuramitz; Amane Terai (Applied Geochemistry, 2025)

Physiological insensitivity to an increase in leaf Fe constitutes a tissue-tolerance mechanism against Fe toxicity in rice - Ida Rosdianti; Yoshiaki Ueda; Hiromi Nakanishi; Dwinita Wikan Utami; Siti Yuriyah; Hideki Takanashi; Matthias Wissuwa (Plant and Soil, 2025)
Aims Iron (Fe) toxicity is a major nutrient stress that severely limits lowland rice yield worldwide. While tolerant rice varieties have been identified, their specific physiological factors underlying the tolerance remain unclear. This study aims to clarify the physiological mechanisms that contribute to field-based Fe stress tolerance. Methods Field trials were conducted at Fe-stressed alongside control sites in Indonesia. Three contrasting lowland Indica rice genotypes were used: Ciherang (sensitive), IR42 (tolerant), and a breeding line KA-28 (tolerant) derived from a cross between Ciherang and IR42. A hydroponic study was conducted to investigate responses of photosynthesis and gene expression. Results In the field experiment, Ciherang exhibited the most severe leaf bronzing, biomass reduction, and > 50% yield loss, whereas IR42 and KA-28 maintained > 60% of control yield with milder symptoms. Sensitive Ciherang and tolerant KA-28 had similar shoot Fe concentrations (> 700 ppm), indicating that tolerance was due to a tissue-based mechanism rather than the exclusion of excess Fe at the root. The hydroponic study confirmed the “tissue-based” tolerance mechanism of KA-28 under Fe toxicity, with less impact of unit Fe on leaf symptoms compared to Ciherang. Reductions in photosynthetic rates and changes in a Fe-responsive vacuolar Fe transporter gene, OsVIT2 , per unit increase in Fe concentrations were more pronounced in Ciherang than in KA-28. Conclusions These findings collectively suggest that the physiological insensitivity to increased Fe levels is the basis for the tissue-tolerance mechanism observed in KA-28 in the field. This study provides valuable insights for breeding Fe-tolerant rice varieties.

Scale evaluation in geothermal fluids by a batch-type method using fiber optic scale sensor - Sakurako Satake; Ai Hosoki; Airi Suka; Yukiko Hoshino; Heejun Yang; Akira Ueda; Hideki Kuramitz; Amane Terai (Geothermics, 2025)

Geochemical study of fluid origin and caprock formation with carbonate mineral precipitation in the Okuaizu geothermal area - Dongyang Mao; Jing Zhang; Yukiko Hoshino; Sakurako Satake; Heejun Yang; Hideki Kuramitz; Akira Ueda; Amane Terai (Geothermics, 2025)

Tissue-free water tritium and non-exchangeable organically bound tritium concentrations in fish near coastline during and after operation of Japan's first nuclear fuel reprocessing facility - Naofumi Akata; Donovan Anderson; Hideki Kakiuchi; Ryohei Yamada; Hidenao Hasegawa; Shinji Ueda (Science of The Total Environment, 2024)

Temporal variation of tritium concentration in monthly precipitation collected at a Difficult-to-Return Zone in Namie Town, Fukushima Prefecture, Japan - Ryohei Yamada; Hidenao Hasegawa; Naofumi Akata; Hideki Kakiuchi; Shinya Ochiai; Haruka Kuwata; Khemruthai Kheamsiri; Shinji Tokonami; Shinji Ueda (Environmental Science and Pollution Research, 2024)

Scattering and intrinsic absorption parameters of Rayleigh waves at 18 active volcanoes in Japan inferred using seismic interferometry - Takashi Hirose; Hideki Ueda; Eisuke Fujita (Bulletin of Volcanology, 2022)

Effect of a proton-pump inhibitor on intestinal microbiota in patients taking low-dose aspirin - Hiroyuki Tsujimoto; Yuki Hirata; Yasuhiro Ueda; Naohiko Kinoshita; Hideki Tawa; Yasuyoshi Tanaka; Ryoji Koshiba; Kazuhiro Ota; Yuichi Kojima; Kazuki Kakimoto; Toshihisa Takeuchi; Takako Miyazaki; et al. (European Journal of Clinical Pharmacology, 2021)

Concentrations of iodine-129 in livestock, agricultural, and fishery products around spent nuclear fuel reprocessing plant in Rokkasho, Japan, during and after its test operation - Yuhi Satoh; Hideki Kakiuchi; Shinji Ueda; Naofumi Akata; Shun’ichi Hisamatsu (Environmental Monitoring and Assessment, 2019)

Relationship between infrasound-derived and buoyancy-derived eruption plume volume estimates - Taishi Yamada; Hiroshi Aoyama; Hideki Ueda (Bulletin of Volcanology, 2018)

Differentiation of Oligodendrocytes from Mouse Induced Pluripotent Stem Cells Without Serum - Sachiyo Misumi; Ruriko Nishigaki; Yoshitomo Ueda; Yoko Watanabe; Yuko Shimizu; Akimasa Ishida; ChaGyun Jung; Hideki Hida (Translational Stroke Research, 2013)

Magma discharge variations during the 2011 eruptions of Shinmoe-dake volcano, Japan, revealed by geodetic and satellite observations - Tomofumi Kozono; Hideki Ueda; Taku Ozawa; Takehiro Koyaguchi; Eisuke Fujita; Akihiko Tomiya; Yujiro J Suzuki (Bulletin of Volcanology, 2013)

Effects of arbuscular mycorrhizal fungi on the abundance of foliar-feeding insects and their natural enemy - Koji Ueda; Keitaro Tawaraya; Hideki Murayama; Satoru Sato; Takashi Nishizawa; Tomonobu Toyomasu; Tetsuya Murayama; Shinpei Shiozawa; Hironori Yasuda (Applied Entomology and Zoology, 2013)

Stress field change around the Mount Fuji volcano magma system caused by the Tohoku megathrust earthquake, Japan - Eisuke Fujita; Tomofumi Kozono; Hideki Ueda; Yuhki Kohno; Shoichi Yoshioka; Norio Toda; Aiko Kikuchi; Yoshiaki Ida (Bulletin of Volcanology, 2013)

Temperature-insensitive reaction in the mammalian circadian clock - Masato NAKAJIMA; Hideki UKAI; Yasushi ISOJIMA; Hiroki R UEDA (Sleep and Biological Rhythms, 2009)

Transient receptor potential (TRP) protein 7 acts as a G protein-activated Ca2+ channel mediating angiotensin II-induced myocardial apoptosis - Shinji Satoh; Haruki Tanaka; Yasuko Ueda; Jun-ichi Oyama; Masahiro Sugano; Hideki Sumimoto; Yasuo Mori; Naoki Makino (Molecular and Cellular Biochemistry, 2007)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Approach for functional analysis of glycan using RNA interference - Shoko Nishihara; Ryu Ueda; Satoshi Goto; Hidenao Toyoda; Hideki Ishida; Mitsuru Nakamura (Glycoconjugate Journal, 2004)

Molecular detection and direct enumeration of methanogenic Archaea and methanotrophic Bacteria in domestic solid waste landfill soils - Ann-Cheng Chen; Kumiko Ueda; Yuji Sekiguchi; Akiyoshi Ohashi; Hideki Harada (Biotechnology Letters, 2003)